2017
DOI: 10.15446/acag.v66n3.57582
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a colloidal system based on avocado (Persea americana Mill. cv. Hass) and others: Effect of process and composition

Abstract: Avocado (Persea americana Mill. cv. Hass), is a perishable fruit, which compositionally presents nutritional benefits, which has led to its productive chain to look for new alternatives of agroindustrialization to improve its competitiveness in the market, being guacamole a potential option. The aim of this research was to evaluate the influence of composition and homogenization process on the colloidal system stability based on avocado and other ingredients for a potential use in the aspersion drying process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Some researchers have reported that when a colloidal system presents a II> 25 mV, there is a strong electrostatic repulsion of the particles, which gives it an adequate physicochemical stability [18], [27], [29] Similar values have been reported for stable guacamole emulsions (II = 27,7 ± 0,3 mV) [51]. Other research has reported superior values in coconut-based colloidal systems (II = 45,6 ± 2,5 mV) [52] and in yacon (Smallanthus sonchifolius) suspensions (II = 33.8±4,0 mV) [27]; however, Marin et al, [53] reported stable blackberry suspensions with probiotics and prebiotics with II = 13.3 ± 0.3 mV.…”
Section: Characterization Of Strawberry-based Suspensionssupporting
confidence: 52%
See 1 more Smart Citation
“…Some researchers have reported that when a colloidal system presents a II> 25 mV, there is a strong electrostatic repulsion of the particles, which gives it an adequate physicochemical stability [18], [27], [29] Similar values have been reported for stable guacamole emulsions (II = 27,7 ± 0,3 mV) [51]. Other research has reported superior values in coconut-based colloidal systems (II = 45,6 ± 2,5 mV) [52] and in yacon (Smallanthus sonchifolius) suspensions (II = 33.8±4,0 mV) [27]; however, Marin et al, [53] reported stable blackberry suspensions with probiotics and prebiotics with II = 13.3 ± 0.3 mV.…”
Section: Characterization Of Strawberry-based Suspensionssupporting
confidence: 52%
“…A consistent behavior was observed with respect to GA and t, increasing the one with the increase of GA and t; on the other hand, the t-GA interaction was positive, denoting the highest µ when the system operates at higher t (5 min) and higher GA (0.4%) (figure 2-1 b). On the other hand, it is considered that cell wall pectin has a synergistic effect with added GA, enhancing at higher t, where a higher release from the cell structure is favored and the values reached are comparatively high compared to banana suspensions (204 Pas) and similar to suspensions of yacon (Smallanthus sonchifolius) (1000 Pas) [27], and avocado emulsions (1034 Pas) [51].…”
Section: Characterization Of Strawberry-based Suspensionsmentioning
confidence: 99%
“…A consistent behavior was observed with respect to GA and t, increasing µ with the increase of GA and t. However, the t-GA interaction was positive, denoting the highest µ when the system operates at higher t (5 min) and higher GA (0.4%). Furthermore, it is known that cell wall pectin has a synergistic effect with added GA, enhancing at higher t, where a higher release from the cell structure is favored, and the values reached are high compared to banana suspensions (204 Pa) and similar to suspensions of yacon (1000 Pa) (López et al, 2009) and avocado emulsions (1034 Pa) (Estrada Mesa et al, 2017).…”
Section: Characterization Of Strawberry-based Suspensionsmentioning
confidence: 99%